Iron Deficiency Risk Factors in Undernourished Children Aged 6-23 Months in Aceh, Indonesia - Ahmad, Aripin; Madanijah, Siti; Dwiriani, Cesilia Meti; Kolopaking, Risatianti (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2018)
The study aimed to analyse both the prevalence and risk factors for iron deficiency in undernourished children aged 6-23 months in Aceh. A cross-sectional study design was applied on 154 underweight children selected through a cluster sampling. Ferritin serum was analysed using the the enzyme-linked immunosorbent assay (ELISA), haemoglobin level using the cyanmethaemoglobin, socio-demographic and food frequency data were collected by interviews. Data on iron intake, dietary diversity and nutrient density were assesed by the repeated 24 hours recall method for three days. The results showed that 27.3% of children suffered from iron deficiency (ID), 50.7% was anaemic and 19.7% suffered from iron deficiency anaemia (IDA). Only 37.7% of children had received exclusive breast milk, 45.5% were given timely introduction of complementary feeding, 33.1% met the minimum meal frequency, 28.6% met dietary diversity, and 23.4% met the criteria for acceptable diet, 33.1% had iron intake from complementary feeding >40% RDA and 24.7% had enough iron density. Age, breastfeeding status and mother’s occupation were significantly associated with the occurrence of ID where children aged 12-23 months were at lower risk than those aged 6-11 months (OR=0.28; 95%CI:0.09-0.83), while children who were not breastfed had 11.33 times higher risk of suffering from ID (OR=11.33; 95%CI:1.38-93.39). Working mothers had 8.29 higher risk of having children with ID (OR=8.29; 95%CI:1.71-40.08). The prevalence of ID in undernourished children was very high, thus it is necessary to improve the quality of breastfeeding and complementary feeding practicess as well as other interventions integrated into reducing malnutrition and iron deficiency to accelerate prevention of malnutrition in children.